157 STAFF MEMBERS' PERSPECTIVES OF HOW TO INCREASE DEMENTIA-FRIENDLINESS IN AN ACUTE IRISH HOSPITAL SETTING. (25th October 2022) - Doyle, C; Davis, A; McNally, S
Abstract: Background: Key principles from The Irish National Dementia Strategy promote accessibility and ease of understanding for those with dementia. Those who provide services and care to people with dementia have a key role to play in identifying gaps in existing service provision. Reduced compliance with National dementia guidelines and overall reduced dementia-friendliness were noted in a hospital-wide audit. It is imperative to seek opinions from those providing direct care to dementia patients on how we can improve dementia-friendliness at a service level. Methods: Random selection was used to distribute staff questionnaires. An open-ended question was used to gather their perceptions on how this hospital can improve its dementia-friendliness at a service level. Results: Forty-seven suggestions were collated across the hospital. Thematic analysis identified 11 different themes; increased staffing, environmental changes, the introduction of dedicated day rooms, increased signage, and introduction of activity boxes were the most common suggestions (68% of answers). Other suggestions included use of sensory items, increased staff education, orientation boxes and improved communication with patients. Conclusion: Healthcare workers have an important role in driving and implementing changes in healthcare settings. Collating staff members' perceptions of improving dementia-friendliness is invaluable given their role in providing services to people with dementia. Implementation of the above-mentioned changes must be explored in order to increase dementia-friendliness, to maintain high-quality service provision, and to ensure compliance with National standards.